Crosslinking characteristics of high density polyethylene by reactive melt processing - Lee, JR; Lee, DG; Hong, SM; Kang, HJ (POLYMER SOC KOREA, 2005)
Reactive melt processing has been carried out to investigate crosslinking characteristics of high density polyethylene (HDPE) with dicummyl peroxide (DCP) and perbutyle pet-oxide (PBP). The increase of torque in the internal mixer indicated that the crosslinking in HDPE has been occurred by peroxides. As a result, the substantial decrease of density, melting temperature, and melt enthalpy were found while the melt viscosity increased in partially crosslinked HDPE. In the mechanical properties of partially crosslinked HDPE, the increase of maximum strength and the decrease in elongation at break were clearly noticed and these were more pronounced when PBP was applied as a crosslinking agent. It seems that the maximum strength was obtained with reactive processing temperature at 150 degrees C, however, the mixing time did not affect to the strength of partially crosslinked HDPE.